The effect of the COVID-19 pandemic on pre-service teachers’ mathematical perceptions and motivation at a selected higher education institution in South Africa - Simayi, Tiny; Tatira, Benjamin (Edelweiss Applied Science and Technology, 2025)
There is a need for knowledge that contributes to the development of educational resilience and enhances the understanding of the complex relationships among teacher education, mathematics educators, and learner outcomes. This study investigated the perceptions and motivation of pre-service teachers in learning mathematics in the post-COVID-19 era. It employed a qualitative research methodology to explore pre-service teachers’ perceptions and motivation. Data were collected through both closed- and open-ended questionnaires from a case study involving twenty pre-service teachers, providing insights into their experiences. The findings indicated significant declines in mathematical performance and motivation to learn mathematics, accompanied by increased anxiety and decreased confidence. Additionally, the study revealed that pre-service teachers face challenges such as limited practice opportunities, lack of group work, and difficulties adapting to e-learning systems. Despite these challenges, they were motivated by factors such as problem-solving skills, creative thinking, and the importance of mathematics in daily life. This research underscores the importance of motivation, adaptation, and support in facilitating effective mathematics learning among pre-service teachers, even under challenging circumstances. The findings have important implications for teacher education programs and policymakers aiming to optimize support for pre-service teachers during times of academic crisis.